A study on the effects of withholding marks and providing written feedback for grade 9 learners who perform poorly in English home language assessments - Barry, Gwen (My University, 2017)
Assessment in education is an extremely important component for both teachers and learners. In a high-stakes environment where marks are all-important both teachers and learners are under immense pressure for all learners to perform well in summative assessment. Teachers want to maximise real learning as well as ensure that their learners achieve good marks. Providing well-structured feedback on assessment tasks is a very effective way of doing this. The salience of this feedback can be further enhanced for weak learners by withholding marks and providing feedback only. This study used an action research model with both quantitative and qualitative data. The conclusions drawn were that when marks are withheld weak learners, in particular, remember and apply comments better. Withholding marks and providing task-oriented comments only results in weak learners improving their work at a faster rate than learners who receive marks and comments together
A research report submitted to the Faculty of Humanities, School of Education at the University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Education.
Keywords: English language--Examinations, questions, etc.; English language--Study and teaching (Secondary); Competency-based education--South Africa